Complete genome sequence of Geodermatophilus obscurus type strain (G-20T). Issue 2 (March 2010) - Ivanova, Natalia; Sikorski, Johannes; Jando, Marlen; Munk, Christine; Lapidus, Alla; Glavina Del Rio, Tijana; Copeland, Alex; Tice, Hope; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; et al.
Abstract Geodermatophilus obscurus Luedemann 1968 is the type species of the genus, which is the type genus of the familyGeodermatophilaceae .G. obscurus is of interest as it has frequently been isolated from stressful environments such as rock varnish in deserts, and as it exhibits interesting phenotypes such as lytic capability of yeast cell walls, UV-C resistance, strong production of extracellular functional amyloid (FuBA) and manganese oxidation. This is the first completed genome sequence of the familyGeodermatophilaceae . The 5, 322, 497 bp long genome with its 5, 161 protein-coding and 58 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.